1991
DOI: 10.1159/000112183
|View full text |Cite
|
Sign up to set email alerts
|

Recent Biochemical and Genetic Advances in Our Understanding of Batten's Disease (Ceroid-Lipofuscinosis)

Abstract: Protein is the major component of the intra-lysosomal storage material which characteristically accumulates in Batten''s disease. In the late-infantile, juvenile and adult forms of the disease, and in a form affecting sheep, this protein is principally composed of a single polypeptide, subunit c of mitochondrial ATP synthase. Subunit c is not stored in the infantile form of Batten''s disease, supporting recent genetic data which suggest this is a distinct disease. Nor is subunit c found in storage material wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Keeping the cytosol clean from consequences of oxidative damage and keeping the protein pool working are functions of the lysosomal and proteasomal systems 38,106–110 . The capacity of these systems decreases over time in postmitotic aging cells, 67,111–115 during oxidative stress, in the progress of pathologic events, 116–119 or in lipofuscinoses, 120,121 which are lysosomal storage diseases including Batten's disease 122–124 . Therefore, some oxidatively damaged proteins are not immediately degraded but further oxidized, resulting in the intracellular accumulation of lipofuscin.…”
Section: The Intracellular Toxicity Of Lipofuscinmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping the cytosol clean from consequences of oxidative damage and keeping the protein pool working are functions of the lysosomal and proteasomal systems 38,106–110 . The capacity of these systems decreases over time in postmitotic aging cells, 67,111–115 during oxidative stress, in the progress of pathologic events, 116–119 or in lipofuscinoses, 120,121 which are lysosomal storage diseases including Batten's disease 122–124 . Therefore, some oxidatively damaged proteins are not immediately degraded but further oxidized, resulting in the intracellular accumulation of lipofuscin.…”
Section: The Intracellular Toxicity Of Lipofuscinmentioning
confidence: 99%
“…38,[106][107][108][109][110] The capacity of these systems decreases over time in postmitotic aging cells, 67,[111][112][113][114][115] during oxidative stress, in the progress of pathologic events, [116][117][118][119] or in lipofuscinoses, 120,121 which are lysosomal storage diseases including Batten's disease. [122][123][124] Therefore, some oxidatively damaged proteins are not immediately degraded but further oxidized, resulting in the intracellular accumulation of lipofuscin.…”
Section: The Intracellular Toxicity Of Lipofuscinmentioning
confidence: 99%
“…Hall et al [39] have found, by immunohistochemical methods, a staining of the intraneuronal-stored material in late-infantile, juvenile and adult NCL with an anti body against subunit c of mitochondrial ATP synthase. No staining was observed in infantile NCL, various stor age diseases and normal ageing brain.…”
Section: Neuropathologymentioning
confidence: 99%
“…It has been shown that the storage material isolated from brains of children with the late infantile type of NCL also contains the same subunit c of mitochondrial ATP synthase [39]. The presence of a common substance in different NCLs could imply that they share similar pathogenetic mechanisms.…”
Section: Biochemistry and Enzymologymentioning
confidence: 99%
“…The human neuronal ceroid-lipofuscinoses are a group of heritable autosomal recessive diseases characterized by severe progressive neurodegeneration which is accompanied by the accumulation of autofluorescent lysosomal storage bodies in neurons as well as in numerous other cell types. Multiple forms of human ceroid-lipofuscinoses can be distinguished by clinical criteria including the age at onset, rate of disease progression, and by the ultrastructure and biochemical composition of the fluorescent storage bodies (Boustany et al, 1988;Dyken and Wisniewski, 1995;Dyken, 1988;Hall et al, 1991a;Haltia et al, 1973;Tyynela et al, 1995). Among the clinical symptoms of these diseases are blindness, seizures, and cognitive and motor decline.…”
Section: Introductionmentioning
confidence: 99%